Analisis Hadis-Hadis Tentang Shalat Jenazah - Siregar, Dame (IAIN Padangsidimpuan, 2019)
Mourners came ready to send janazah. Janazah was immediately washed, then placed at home in the position of respect. Excavation of the grave as soon as possible, so as not to be blocked as soon as possible. Janazah prayer can be carried out either at home or at the mosque. Thus eating in janazah will be avoided, unless you are far away from the place. The number of people who were supposed to send him 100 people was later buried. Imam Solat Janazah is the best reading is not a child or close close that is not good reading. The ghoib prayer may be for those who do not have time to go to the janazah place, or have been buried near the janazah tomb. The position of the priest for the male janazah is about the shoulder, the woman is at the center, and the position of the janazah is on the right side of the male or female. All mourners should practice janazah prayer, not dating only to recite Yasin, takhtiman tahlilan and prayer. After the janazah was escorted to the mosque, there was a habit of a part of the community of the women eating together provided by Family Janazah. Then it would be nice to pray for the janazah at home, it is very possible to reach 100 people quickly, rather than at the mosque. The implementation was at 06.30 school children, then teenagers, mothers and fathers and delivered them to the funeral. So the positive is that children and teenagers are able to pray janazah. Because the community has many activities that need to be completed such as the teacher to teach and other activities